Case fatality rate and fatal bleeding complication in patients with pulmonary embolism and patent foramen ovale. (14th October 2021) - Hobohm, L; Schmitt, V H; Munzel, T; Konstantinides, S V; Keller, K
Abstract: Objectives: In patients with acute pulmonary embolism (PE), right atrial pressure is elevated, which increases risk for right-to-left shunt when patent foramen ovale (PFO) is present and thus potentially increases risk for paradoxical embolism. Little is known about the clinical outcome of patients with PE and concomitant PFO. Methods: We analysed data on patient characteristics, treatments and in-hospital outcomes for all PE patients (ICD-code I26) with concomitant presence of PFO in Germany 2005–2018 (source: Research Data Center (RDC) of the Federal Statistical Office and the Statistical Offices of the federal states, DRG Statistics 2005–2018, and own calculations). Results: Between January 2005 and December 2018, 1, 174, 235 patients with acute PE (53.5% females) were included in this analysis; of those, 5, 486 (0.5%) had a concomitant diagnosis of PFO. Trends analysis demonstrating an increasing frequency of diagnosed PE with additional PFO from 2005 (n=299) to 2018 (n=556; p<0.001). While patients with PE and PFO presented more often with signs of haemodynamic compromise such RV dysfunction (37.6% vs. 28.5%) or shock (7.1% vs. 3.9%) as well as paradox arterial emboli (47.8% vs. 3.2%) or intracerebral bleeding (3.3% vs. 0.6%), PE patients with PFO died less often compared to PE patients without PFO (11.1% vs. 15.8%). Patients with PE and PFO were younger (65 [IQR 52–75] vs. 72 [60–80]; P<0.001) and were more often treated invasively with a reperfusion treatment approach like embolectomy (10.2% vs. 4.2%) or systemic thrombolysis (5.0% vs 0.1%). A multivariate logistic regression analysis revealed a 27.6-fold increased risk for paradox arterial emboli (OR, 27.6 [95% CI 26.1–29.1]; p<0.001) and a 3.9-fold increased risk for intracerebral bleeding events (OR, 3.9 [95% CI 3.3–4.54]; p<0.001) for patients with PE and concomitant PFO. In normotensive patients with RVD and PFO, embolectomy were not associated to affect the rate of intracerebral bleeding events (OR, 0.8 [95% CI 0.2–2.6]; p=0.720) compared to conventional non-reperfusion treatment; instead of systemic thrombolysis, which is associated with a higher risk of intracerebral bleeding (OR, 3.5 [95% CI 1.8–6.59]; p<0.001) compared to conventional non-reperfusion treatment. Conclusion: Patients with acute PE and the concomitant presence of PFO are associated with a high risk for paradox arterial emboli and intracranial bleeding events. Especially in normotensive patients, the use of systemic thrombolysis should be considered with cautious. Thus, our findings may improve the clinical management of patients with PE and PFO. FUNDunding Acknowledgement: Type of funding sources: None.